The Response of Microbial Communities to Peatland Drainage and Rewetting. A Review - Kitson, Ezra; Bell, Nicholle G. A. (Frontiers in Microbiology, 2020)
Peatlands are significant global carbon stores and play an important role in mediating the flux of greenhouse gasses into the atmosphere. During the 20th century substantial areas of northern peatlands were drained to repurpose the land for industrial or agricultural use. Drained peatlands have dysfunctional microbial communities, which can lead to net carbon emissions. Rewetting of drained peatlands is therefore an environmental priority, yet our understanding of the effects of peatland drainage and rewetting on microbial communities is still incomplete. Here we summarise the last decade of research into the response of the wider microbial community, methane-cycling microorganisms, and micro-fauna to drainage and rewetting in fens and bogs in Europe and North America. Emphasis is placed on current research methodologies and their limitations. We propose targets for future work including: accounting for timescale of drainage and rewetting events; better vertical and lateral coverage of samples across a peatland; the integration of proteomic and metabolomic datasets into functional community analysis; the use of RNA sequencing to differentiate the active community from legacy DNA; and further study into the response of the viral and micro-faunal communities to peatland drainage and rewetting. This review should benefit researchers embarking on studies in wetland microbiology and non-microbiologists working on peatland drainage and rewetting in general.